Standard material transfer agreement - Food and Agriculture Organization of the United Nations (Food and Agriculture Organization of the United Nations, 2006)
WHEREAS the International Treaty on Plant Genetic Resources for Food and Agriculture (hereinafter referred to as "the Treaty")1 was adopted by the Thirty-first session of the FAO Conference on 3 November 2001 and entered into force on 29 June 2004; The objectives of the Treaty are the conservation and sustainable use of Plant Genetic Resources for Food and Agriculture and the fair and equitable sharing of the benefits arising out of their use, in harmony with the Convention on Biological Diversity, for sustainable agriculture and food security; The Contracting Parties to the Treaty, in the exercise of their sovereign rights over their Plant Genetic Resources for Food and Agriculture, have established a Multilateral System both to facilitate access to Plant Genetic Resources for Food and Agriculture and to share, in a fair and equitable way, the benefits arising from the utilization of these resources, on a complementary and mutually reinforcing basis..